Financial Structure and Operating Efficiency of Housing Cooperative Societies - Kalundu Kimanzi; Mirie Mwangi; Duncan Elly Ochieng; Josephat Lishenga (European Scientific Journal, ESJ, 2019)
Housing co-operatives contribute to the social-economic growth of a country. They are voluntary in concept and owner-user and based on members’ loyalty. Therefore, this study sought to establish the relationship between financial structure and operating efficiency on housing co-operative Societies in Nairobi City County, Kenya. The data collection form was used to record data of all the elements of financial structure and operating efficiency from audited financial statements. Housing co-operatives, which constituted 50.3% of response rate were analysed using a two-stage process: data envelopment analysis and regression analysis. The first stage involved the use of DEA model to compute the efficiency scores, which were regressed in the second stage using linear regression analysis. The results from DEA output indicate that most of the housing co-operatives were inefficient while the regression results indicated that a positive and significant relationship existed between financial structure and operating efficiency. Therefore, this study recommends that housing co-operatives should formulate strategies that would grow their operations to reduce operational costs and enhance management efficiency. Besides, there is a need for housing co-operatives' boards of directors to make prudent investment decisions that would help members’ maximize social and economic goals.